(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2009)
Internal control is system,defined and implemented under its responsibility , which aims to ensure that; laws and regulations are complied with; the instructions and directional guidelines fixed by Executive Management or the Management Borad are applied; the company internal processes are functioning correctlly , particularly those implicating the security of its assets; Financial Information is reliable; and generally contributes to the control over its activities , to the efficiency of its operation and to the efficient utilisation of its Resources. By helping to anticipate and control the risks involved in not meeting the objectives the company has set for itself, the internal control system plays akey role in conducting & monitoring its various activities. However , internal control can not provide an absoulute guarantee the bankes objectives will be met under the Accounting Information Systems.Five variables had been used from the internal control system goals in the quastoiner application to know the role of the internal control in the banks, and the statistical analysis results was leading to the truely and correctly of the information in the first level coming next the others variable targets .